Bahan Ajar Transformasi Geometri Berbasis Discovery Learning melalui Pendekatan Etnomatematika - Dwi Nur Fitriyah; Handoko Santoso; Nurain Suryadinata (Universitas Hamzanwadi, 2018)
The purpose of this research is to produce discovery learning based materials through ethnomathematics approaches on geometry transformation materials (valid, practical, and effective) and according to the needs of students. The type of this research is Research and Development (R D) by using Plomp Model which consists of five stages: prelimenary investigation; realization/construction; test, evaluation and revision; dan implementation. The instruments were used the form of validation questionnaire, student response sheet, observation sheet of teaching materials implementation, and achievement test. Based on the research, the result of the validation of experts with the percentage of 83% (very valid), 84.50% (very practical), and the effectiveness of 85.71% (high). Based on this development research the advantages of teaching materials are material materials related to the ethnomathematics of Batik Lampung pattern on the application of the concept of geometry transformation. The weakness of teaching materials developed is that the material discussion is limited to the type of geometry transformation and its effective test is only based on the KKM. Further product development, teaching materials can cover the entire material of geometry transformation with other Lampung culture ethnomathematics studies and effectiveness tests are thoroughly tested from learning outcomes, activities and learners' abilities.